La gestion des conflits d'intérêt dans un jury de thèse de doctorat - Ridde, Valéry (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
A researcher or university professor is often required to be a member of a thesis jury. This is part of their scientific activities. However, in an increasingly specialized academic world, it is sometimes difficult to create a thesis jury without being confronted with conflicts of interest between the members and the supervisory team. While in recent years some universities have organized processes to manage these conflicts, others have not yet decided. This case study adapts several real-life situations to show the challenges of such conflict of interest management in setting up a doctoral thesis jury.